Iterative learning control optimization strategy for feedback control systems with varying tasks - Chen, Fangmei; Tao, Hongfeng; Zhuang, Zhihe; Paszke, Wojciech (1975- ); Stojanovic, Vladimir
Iterative learning control (ILC) combined with feedback control is a common approach to repetitive systems with external disturbances, as it enables high tracking performance and guarantees time-domain stability. However, the variation of the reference trajectory in practical repetitive operations often degrades the control performance.
Keywords: iterative learning control; feedback control; parallel structure; performance optimization; varying task